EDUKASI TATA RIAS KOREKTIF UNTUK MENINGKATKAN KETERAMPILAN PEKERJA MIGRAN DI GAYATRI BEAUTY ACADEMY, SINGAPURA - Puspa Arum, Aniesa; Ayuningtyas, Nurina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Partner problems: 1) Limited knowledge about corrective facial makeup to support activities, 2) Limited media regarding corrective facial makeup as an alternative learning source. We facilitate solutions to problems by 1) Providing education about corrective facial makeup to support appearance, 2) Developing a pocketbook about corrective facial makeup as an alternative learning resource. The objectives of this activity: 1) Increase knowledge of the basic concepts of corrective facial make-up, 2) Stimulate creativity in applying corrective facial make-up according to facial conditions. The method of carrying out activities is lectures accompanied by case studies, discussions, demonstrations and guided practice at the Gayatri Beauty Academy, Singapore which will be held on August 27, 2023. The implementing team is lecturers from the Cosmetology Education Study Program, Jakarta State University, with a target of 20 migrant workers. Activities are carried out in stages with several achievement targets tailored to the needs, characteristics of the participants and the learning objectives to be achieved. Data collection instruments are: 1) Objective tests to measure knowledge, and 2) non-tests, in the form of performance sheets to measure skills and questionnaires to measure participants' attitudes/satisfaction. This activity showed positive results seen from: 1) the knowledge aspect of 20 participants got an average score of 85, which means they were able to absorb the material presented well, 2) the skills aspect of 17 participants (85%) got a score of 90, which means they were able to apply the rules. corrective facial makeup according to facial condition, 3) attitude aspect, as many as 90% of participants hope that similar activities can continue. It can be concluded that education about corrective facial makeup can improve participants' skills because it provides benefits and opportunities to open a business. Abstrak Permasalahan mitra:1) Terbatasnya pengetahuan tentang tata rias wajah korektif untuk menunjang aktivitas,2) Keterbatasan media tentang tata rias wajah korektif sebagai sumber belajar alternatif. Solusi permasalahan kami memfasilitasi dengan:1) Memberikan edukasi tentang tata rias wajah korektif guna menunjang penampilan,2) Mengembangkan buku saku tentang tata rias wajah korektif sebagai sumber belajar alternatif. Tujuan kegiatan ini:1) Meningkatkan pengetahuan mengenai konsep dasar tata rias wajah korektif, 2) Merangsang kreativitas penerapan tata rias wajah korektif sesuai kondisi wajah. Metode pelaksanaan kegiatan dengan ceramah disertai studi kasus, diskusi, demostrasi dan praktik terbimbing bertempat di Gayatri Beauty Academy, Singapura yang dilaksanakan pada tanggal 27 Agustus 2023. Tim pelaksana dosen Program Studi Pendidikan Tata Rias, Universitas Negeri Jakarta, dengan sasaran pekerja migran berjumlah 20. Kegiatan dilaksanakan secara bertahap dengan beberapa sasaran capaian yang disesuaikan dengan kebutuhan, karakteristik peserta dan tujuan pembelajaran yang ingin dicapai. Instrumen pengumpulan data berupa: 1) Tes objektif untuk mengukur pengetahuan, dan 2) Non tes, berupa lembar unjuk kerja guna mengukur keterampilan dan kuesioner untuk mengukur sikap/kepuasan peserta. Kegiatan ini menunjukan hasil positif dilihat dari: 1) aspek pengetahuan dari 20 peserta memperoleh nilai rata-rata 85 yang artinya mampu menyerap materi yang disampaikan dengan baik, 2) aspek keterampilan sebanyak 17 peserta (85%) memperoleh nilai 90 yang artinya mampu menerapkan tata rias wajah korektif sesuai kondisi wajah, 3) aspek sikap, sebanyak 90% peserta berharap kegiatan sejenis dapat berlanjut, dapat disimpulkan bahwa edukasi tentang tata rias wajah korektif dapat meningkatkan keterampilan peserta karena memberikan manfaat dan peluang untuk membuka usaha.